Sexuality in Older Adults (65+)—An Overview of The Recent Literature, Part 2: Body Image and Sexual Satisfaction. Issue 1 (2nd January 2017) - Træen, Bente; Carvalheira, Ana; Kvalem, Ingela Lundin; Štulhofer, Aleksandar; Janssen, Erick; Graham, Cynthia A.; Hald, Gert Martin; Enzlin, Paul
ABSTRACT: Objectives : the aim of the paper is to provide an overview of the literature published 2005-2015 on sexual satisfaction and body image in older adults. Method : A narrative literature search using the PsycINFO database was conducted. Results : Although women in general seem less satisfied with their bodies than men, particularly in sexual contexts, older women appear to be less vulnerable to body-related dissatisfaction than younger women. Despite the age-specific dynamics of sexual satisfaction and sexual well-being, which parallel age-related decrease in the frequency of sexual activity, research findings from different countries show that substantial proportions of aging men and women are satisfied with their sex life. There is some limited evidence that this proportion may be increasing across cohorts. Gender differences in factors that influence sexual satisfaction among older adults appear marginal. Conclusion : Older age can affect sexual satisfaction on individual, interpersonal, and culture-related levels. Future research in older adults' sexuality should focus on sexual well-being in women who are without partners, sexual satisfaction among aging lesbian, gay, bisexual, and transgender individuals and couples, the relationship between religiosity and sexual satisfaction, and employ a comparative, cross-cultural approach.